2017
DOI: 10.1039/c7cp01947e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry of Mg substitution in NaMnPO4olivine: concentration limit and cation distribution

Abstract: Metal ion substitution in phospho-olivines is an effective way to improve their performance as electrode materials in lithium ion and alternative sodium ion batteries. In this contribution, we examine in detail the crystal structure of Mg-substituted NaMnPO. The preferential occupancy of the alkaline M1 position by Mg ions has been found for the first time - a phenomenon which appears to be opposite to the case of Mg-substituted LiMnPO, where Mg and Mn reside in the M2 position. Mg solubility in NaMnPO is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Mg solubility in NaMnPO 4 is limited in the mole ratio range of 0. www.advancedsciencenews.com < 0.15. [155] NaMnPO 4 /C composite was prepared through an ion-exchange reaction and ball milling processes. [156] The as-prepared compound consists of well-crystallized olivine-phase NaMnPO 4 with disordered carbon species and no antisite defects, delivering a reversible capacity between 80 and 85 mAh g −1 in model lithium cells (Figure 13b).…”
Section: Sodium Iron/manganese Phosphates and Iron/manganese Fluorophmentioning
confidence: 99%
“…Mg solubility in NaMnPO 4 is limited in the mole ratio range of 0. www.advancedsciencenews.com < 0.15. [155] NaMnPO 4 /C composite was prepared through an ion-exchange reaction and ball milling processes. [156] The as-prepared compound consists of well-crystallized olivine-phase NaMnPO 4 with disordered carbon species and no antisite defects, delivering a reversible capacity between 80 and 85 mAh g −1 in model lithium cells (Figure 13b).…”
Section: Sodium Iron/manganese Phosphates and Iron/manganese Fluorophmentioning
confidence: 99%
“…Recently we have demonstrated that the Mg solubility in NaMnPO 4 is restricted up to 15 mol%. 8 This is in contrast to the lithium analogues, forming solid solutions having compositions such as LiMn 1Àx Mg x PO 4 without any concentration constrains. 9,10 The difference between Mg-substituted NaMnPO 4 and LiMnPO 4 analogues arises from their structure peculiarities.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The difference between Mg-substituted NaMnPO 4 and LiMnPO 4 analogues arises from their structure peculiarities. 8 For sodium manganese phospho-olivine, it is found out that Mg 2+ occupies preferentially M1 olivine site instead of the usual M2 sites and the magnesium charges are compensated by creation of corresponding metal vacancies in the M1 position: [Na 1À2x/(1Àx) Mg x/(1Àx) ] M1 [Mn] M2 PO 4 . 8 In lithium manganese phospho-olivine, Mg 2+ ions substitute the Mn 2+ ions, which leads to a signicant improvement in the electrochemical performance of LiMnPO 4 due to a reduction of the lattice mismatch between the lithiated and delithiated phases, as well as to a modication of the Mn 3+ /Mn 2+ redox couple.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations